Supermarkets and the organic food supply chain: the potential for waste generation and its mitigation. (18th January 2007) - Patel, Avani; Woodward, David G
This paper discusses the role of multiple grocery retailers ('supermarkets') within the organic food industry. While the background to the object industry (in terms of both the incentive(s) to buy organic food and the ensuing market demand/supply statistics) has to be presented such as to justify the topic as one worthy of academic interest, the main concern of this paper is with the potential within the relevant industry for waste generation to occur. The potential for such an eventuality is identified via a detailed analysis of: the industry's attempts to ensure the integrity of its organic supplies via the imposition of standards that exceed mandatory (hence EU) requirements, thus potentially exerting pressure on suppliers; the pricing policies applied by the supermarkets; the extent of their domestic sourcing versus imports; the GM 'contamination' debate and supplier cooperation via advice, research and the encouragement of partnership schemes. A critique of the present situation regarding all these issues is combined with an analysis of present initiatives to reduce the incidence of waste that might erstwhile occur, together with suggestions for further improvements – although ultimately it appears likely that 'mitigation' is a more likely future scenario than 'minimisation'.